2002
DOI: 10.1034/j.1600-0854.2002.30503.x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI Binds to and Localises with Dab2, Potentially Linking Receptor‐Mediated Endocytosis and the Actin Cytoskeleton

Abstract: Myosin VI, an actin-based motor protein, and Disabled 2 (Dab2), a molecule involved in endocytosis and cell signalling, have been found to bind together using yeast and mammalian two-hybrid screens. In polarised epithelial cells, myosin VI is known to be associated with apical clathrin-coated vesicles and is believed to move them towards the minus end of actin filaments, away from the plasma membrane and into the cell. Dab2 belongs to a group of signal transduction proteins that bind in vitro to the FXNPXY seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
245
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 226 publications
(252 citation statements)
references
References 44 publications
7
245
0
Order By: Relevance
“…To verify the novel MYO6 interaction network, we introduced mutations into the known cargo‐binding and lipid‐binding sites, the WWY, RRL and PIP 2 binding motifs 10, 11, 14 and assessed differences in the relative abundance of BirA*‐MYO6 binding partners using a SILAC‐based approach (Fig 1F). Analysis of these cells by confocal microscopy also revealed that the ΔRRL and ΔPIP2, but not the ΔWWY mutation, perturbed MYO6 targeting to APPL1 endosomes (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the novel MYO6 interaction network, we introduced mutations into the known cargo‐binding and lipid‐binding sites, the WWY, RRL and PIP 2 binding motifs 10, 11, 14 and assessed differences in the relative abundance of BirA*‐MYO6 binding partners using a SILAC‐based approach (Fig 1F). Analysis of these cells by confocal microscopy also revealed that the ΔRRL and ΔPIP2, but not the ΔWWY mutation, perturbed MYO6 targeting to APPL1 endosomes (Fig EV1A).…”
Section: Resultsmentioning
confidence: 99%
“…These interactions occur at two major protein binding motifs, the RRL and WWY (named after their amino acid composition), which are located within two distinct subdomains of a unique C‐terminal cargo‐binding tail 10, 11. The tail also contains a phosphatidylinositol 4,5‐bisphosphate (PIP 2 ) binding motif, which aids recruitment of the motor to membranes along with its binding partners 14.…”
Section: Introductionmentioning
confidence: 99%
“…Dab2 contains a conserved N-terminal phosphotyrosine-binding domain (Yun et al, 2003) that binds to members of the low-density lipoprotein receptor (LDLR) family and with phosphoinositides (Morris and Cooper, 2001). Its linker and C-terminal regions bind clathrin, the clathrin adaptor protein AP2 and myosin VI, facilitating clathrincoated pit assembly and receptor-mediated endocytosis (Morris and Cooper, 2001;Mishra et al, 2002;Morris et al, 2002). The endocytic and vesicular trafficking functions of Dab2 are postulated to mediate its effects on cellular signaling (Morris et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Its linker and C-terminal regions bind clathrin, the clathrin adaptor protein AP2 and myosin VI, facilitating clathrincoated pit assembly and receptor-mediated endocytosis (Morris and Cooper, 2001;Mishra et al, 2002;Morris et al, 2002). The endocytic and vesicular trafficking functions of Dab2 are postulated to mediate its effects on cellular signaling (Morris et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferase (GST)-fusion proteins were expressed and purified onto glutathione-Sepharose 4B beads (Amersham Biosciences) as described previously (Morris et al, 2002) with pull-down assays performed using 250 g Triton lysis buffer cell lysates and 5 g of GST or GST-fusion. After 2 h of sample incubation end-over-end at 4°C, proteins specifically bound to the GST-fusion coupled to the Sepharose beads were washed extensively with lysis buffer and processed as described above.…”
Section: Immunoprecipitation and Pull-down Assaysmentioning
confidence: 99%